Optimization of Building Configuration in Vertical Residential Housing towards Outdoor Thermal Comfort: Case Study of Tambora Flats, Jakarta, Indonesia - Khairani Ayu Rizqi; Budi Prayitno (Universitas Gadjah Mada, 2020)
Population growth in Indonesia is not offset by the construction of urban facilities and infrastructure and the improvement of urban services. In densely populated urban areas with narrow residential conditions, the demand for shelter is higher, causing an increase in the price of land and housing. One of the efforts in responding to this problem in the Special Capital Region of Jakarta is to build vertical residential or flats. This study aimed to determine the level of outdoor thermal comfort of Tambora flats in Jakarta, which have air temperatures ranging 26–29°C and air humidity of 76–92%. Existing flats were simulated with the Envi-MET 3.1 software, with the first stage being to determine the height of the building and material of the building, the street, and then assessing the existing outdoor thermal comfort level by inputting climatic data. Overall, the thermal comfort index values of both existing and planned model building configurations of Tambora flats and its surrounding area were at the standard level for a humid climate. Of our models, model B had the best potential to provide thermal comfort to humans in the area of the flats. In order to implement the proposed model building configuration with optimal outdoor thermal comfort in real buildings, future research should focus on a wider range of aspects, including diversity and density of buildings, and neighborhood type.